PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE (ESG) TERHADAP FINANCIAL PERFORMANCE & NON FINANCIAL PERFORMANCE PERUSAHAAN (Studi Empiris pada Indeks Kompas 100 yang mengungkapkan ESG Score dan Terdaftar di BEI Tahun 2020-2022) - Sitepu, Mery Shinta Serafim; Utomo, Dwi Cahyo (Diponegoro Journal of Accounting, 2024)
This study aims to assess the influence of Environmental, Social, and Governance (ESG) Disclosure on both financial and non-financial performance. The dependent variables in this research are Financial Performance and Non- Financial Performance, with independent variables involving environmental disclosure, social disclosure, and governance disclosure. Financial performance is measured using proxies such as ROA (Return on Assets), ROE (Return on Equity), and Tobin’s. Non-financial performance is assessed using a single proxy, which is market shares.    The data for this study are sourced from the financial reports of companies listed in the Kompas 100 index on the Indonesia Stock Exchange (BEI) during the period 2020-2022. The research observation, consisting of 195 companies over three consecutive years, was selected using purposive sampling. Multiple linear regression analysis was employed to test the research hypotheses.    Using a multiple linear regression model, it is possible to determine the relationship between environmental disclosure, social disclosure, and governance disclosure with both financial performance and non-financial performance of companies. The findings of this study indicate that environmental disclosure, social disclosure, and governance disclosure have a non-significant and negative determination with financial performance. The results also reveal that environmental and social disclosure exhibit a non-significant and negative determination with non- financial performance. However, governance disclosure demonstrates a positive and significant determination with non-financial performance.